2010
DOI: 10.1097/brs.0b013e3181cdd1aa
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Analysis of Newly Developed Degenerative Spondylolisthesis in a Mean Twelve-Year Prospective Study

Abstract: This was the first study to confirm the relationship of PI and the development of DS in a long-term prospective observation. Proposed pathogenetic differences might explain the fact that L4-DS is far more prevalent than L3-DS. The development of DS could be predicted by baseline lumbopelvic morphology among the highly susceptible perimenopause women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 37 publications
5
43
1
3
Order By: Relevance
“…The results indicated that the PI was a predisposing factor in the pathogenesis and development of DS [12,13,16], supporting the theory that a greater PI implied a greater SS and as a result of a greater LL. The increased LL resulted in greater shear forces at the lumbosacral junction which may increase the risk of presenting or developing spondylolisthesis.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The results indicated that the PI was a predisposing factor in the pathogenesis and development of DS [12,13,16], supporting the theory that a greater PI implied a greater SS and as a result of a greater LL. The increased LL resulted in greater shear forces at the lumbosacral junction which may increase the risk of presenting or developing spondylolisthesis.…”
Section: Introductionsupporting
confidence: 63%
“…Spinopelvic sagittal alignment accompanied with biomechanical changes has been demonstrated in previous studies in the pathogenesis and development of lumbar degenerative diseases [12][13][14][15][16][17]24]. Several studies have compared the sagittal spinopelvic alignment in LDD or LDH patients with the asymptomatic volunteers, suggesting that the sagittal profile in these patients was characterized by a straight spine (lower LL and TK), vertical sacrum (lower SS and greater SFD) with an anterior displaced C7 plumb line (greater SVA) [13][14][15].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Aono et al [ 20 ] and Barrey et al [ 21 ] have demonstrated that patients with degenerative spondylolisthesis have a higher pelvic incidence than controls. Another study [ 22 ] compared the spinopelvic parameters of patients with isthmic spondylolisthesis and degenerative spondylolisthesis.…”
Section: Axial Pain From Sagittal Imbalancementioning
confidence: 99%
“…1 The estimated incidence of DLS is 12.7% with an overall prevalence of 6% that increases between the fifth and eighth decades of life. [2][3][4] For symptomatic patients, the recent Spine Patient Outcomes Research Trial (SPORT) -DLS study has demonstrated that surgical management is superior to conservative care at 2 and 4 years post-intervention. 5,6 From a surgical perspective, since the controlled study by Herkowitz and Kurz 7 demonstrated a high failure rate following decompression (conventional midline laminectomy) alone (D), decompression and fusion (DF) has become the surgical treatment of choice for patients with DLS.…”
mentioning
confidence: 99%